2014
DOI: 10.1200/jco.2014.32.3_suppl.566
|View full text |Cite
|
Sign up to set email alerts
|

Multi-institutional assessment of sphincter preservation for rectal cancer.

Abstract: BACKGROUND-Sphincter preserving surgery (SPS) has been proposed as a quality measure for rectal cancer (RC) surgery. However, previous studies on SPS-rates lack critical clinical characteristics, rendering it unclear if variation in SPS-rates is due to unmeasured case-mix differences or surgeons' selection criteria. In this context, we investigate the variation in SPS-rates at various practice settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…In our study, a permanent stoma was created in about one‐quarter of patients with mid or low rectal cancer, which included patients who underwent APR as initial surgery (15.4%) and patients in whom a permanent stoma was created after SPS (11.3%). The APR rate was lower than that of previous studies, where it ranged from 23.4% to 41% .…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…In our study, a permanent stoma was created in about one‐quarter of patients with mid or low rectal cancer, which included patients who underwent APR as initial surgery (15.4%) and patients in whom a permanent stoma was created after SPS (11.3%). The APR rate was lower than that of previous studies, where it ranged from 23.4% to 41% .…”
Section: Discussioncontrasting
confidence: 82%
“…Our subgroup analyses showed that tumour distance from the anal verge was the only predictor of permanent stoma creation not only in APR as initial surgery but also after SPS as initial surgery. Postoperative factors, such as surgical complications and recurrence, were significant factors in prior studies evaluating permanent stoma after SPS , and tumour distance from the anal verge was a significant predictor of APR as initial surgery . The fact that tumour distance is a predictor of permanent stoma after SPS in our study may be explained by prior findings that lower tumour height is associated with local recurrence and surgical complications .…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations